Διαχείριση δικτύων αποχέτευσης στην Κύπρο με τη χρήση γεωπληροφορικής - Αλεξάνδρου, Γεωργία (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The aim of the dissertation is to analyze the steps that need to be followed so as to implement digitization on a sewerage system. This analysis will be presented through the analysis of the digitalization of the sewerage network of the Municipality of Latsia. Modeling the sewer system is a valuable tool for evaluating the management of storm water and wastewater alike. This paper proposes models that are suitable for development in all areas of Cyprus which are integrated into the sewer system. The results presented in this dissertation where achieved via digitizing the sewer system of Latsia Municipality, including the blotted center conductor, the wells of the center conductor and the housing as well as the connections of the central conduit houses. The same process can be followed in all areas included in the sewer system in Cyprus. If this occurs, there are many ways in which the collected data can be applied for their management and development. This dissertation primarily focuses on sewerage systems, both in Cyprus and abroad. The first chapter deals with the existing environmental legislation and policies, environmental authorities as well as the current situation in Cyprus. The second chapter presents examples of similar digitization work from abroad, Greece and Cyprus. The third chapter explains the details of the sewerage network digitization process as well as its results. Lastly, the final chapter presents the results and benefits of implementing data digitization on an organization such as SBN (Sewerage board of Nicosia), as well as some proposals of exploiting such data. In addition, the final chapter presents a list of the equipment used to obtain all necessary information from the field, and the appropriate software which will be used for handling office procedures.
Keywords: Geographic information systems; Network sewerage; Digitization; Equipment; Software; Γεωγραφικά συστήματα πληροφοριών; Δίκτυο αποχέτευσης; Ψηφιοποίηση; Εξοπλισμός; Λογισμικά